Semantic Repository in Internet Infrastructure knowledge domain: Methodology Position Paper - Braga, Julião; Omar, Nizam (Anais do Workshop Pré-IETF (WPIETF), 2014)
This is a position paper that proposes the development of a methodology to build Semantic Repositories in the Internet Infrastructure domain.